Promoting Positive Leadership. Issue 143 (17th September 2013) - Mather, Peter C.; Hess, Michael
Abstract: Drawing from positive organizational scholarship, the authors describe strategies for moving from an ineffective focus on problems to leveraging organizational strengths for productive change.